Changes in temperament over time in young children with autism spectrum disorder and other developmental delays: a follow‐up comparison study. Issue 10 (6th June 2019) - Reyes, N.; Walsh, C.; Soke, N.; Hepburn, S.
Abstract: Background: Although in the last decade some research has emerged on temperament in autism spectrum disorder (ASD), this research has primarily focused on the differences between children with ASD and their typically developing peers rather than the stability or change in temperament in this population. Thus, the goal of this study was to examine temperament over time in children with ASD, developmental delays (DD) and typical development (TD). Temperament differences were also compared among the three groups. Methods: To accomplish this, parents rated children's temperament at Time 1 (T1) and Time 2 (T2) using the Carey Temperament Scales (CTS). Results: Results from the study showed that at T1, parents of children with ASD rated their children as more withdrawn (i.e. approach), and emotionally negative (i.e. mood), and less distractible and adaptable than parents of children with TD and DD. Also, children with ASD were rated as more intense and children with DD as less distractible than their TD peers. Similarly, at T2, children with ASD were rated more withdrawn, and emotionally negative, and less persistent, rhythmic, adaptable and distractible than children with TD and DD. Also, children with ASD were rated as more active than their DD peers. Regarding stability, parent ratings of temperament appeared stable over time in the TD group, but ratings varied substantially in the ASD or DD groups. That is, for the ASD group, activity and approach at T1 were significantly associated with their corresponding dimensions at T2. However, for the TD group, rhythmicity, approach, intensity and mood at T1 were significantly associated with those dimensions at T2. No associations were found in the DD group. Regarding change, parents reported change in rhythmicity, persistence and threshold between T1 and T2 in the ASD group. Similarly, parents reported change in rhythmicity, approach and threshold between T1 and T2 in the DD group. Lastly, parents of TD children reported change in adaptability, persistence and distractibility between T1 and T2. Conclusions: These findings are novel in that children with ASD appear to have less stable temperament profile and different change patterns than children with TD or DD. Similar to previous research, children with ASD were described by their parents as experiencing more temperamental difficulties.